A Transperineal Approach to Hysterectomy of a Retained Didelphic Uterine Horn. Issue 3 (September 2017) - Mullen, Mary M.; Kuroki, Lindsay M.; Hunt, Steven R.; Ratkowski, Kristy L.; Mutch, David G.
Abstract : BACKGROUND: Gynecologic surgeries are performed through abdominal, vaginal, laparoscopic, or robot-assisted laparoscopic routes. However, if the pelvis is not accessible by one of these routes, there are no published reports to guide pelvic surgeons. CASE: A 34-year-old conjoined twin status postseparation with uterine didelphys and absence of her left colon and sacrum underwent hemihysterectomy, at which time her müllerian anomaly was unknown. She re-presented with vaginal bleeding and pain eventually attributed to a retained uterine horn. Conservative management failed. Given dense adhesions, traditional approaches to hysterectomy were not successful. She underwent a transperineal hemisupracervical hysterectomy. CONCLUSION: We propose a novel approach to the pelvis to guide surgeons when traditional approaches are not feasible. We also describe an instance of a retained uterine didelphys horn. Abstract : Given the inability to access the pelvis owing to dense adhesions, a transperineal hemisupracervical hysterectomy of a retained didelphic uterine horn was performed.